The Effect of Contribution, Role, and Capital on MSMEs Business Development in Islamic Banks with Human Resources Quality as A Moderation Variable - Sri Fitri Wahyuni; Muhammad Shareza Hafiz; Riyan Pradesyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aims to see the effect of the contribution, role, and venture capital on MSMEs business development, with the quality of human resources as a mediating variable. This research was conducted at Islamic banks in the city of Medan, with a sample of 160 people. As for the results obtained based on the results of the path coefficient test carried out, it was found that there were 3 significant items on construction with t-statistic values ​​> 1.65 and p-values ​​< 0.05, meaning that the hypotheses H4, H6, and H7 were accepted, that there was a significant influence of business capital with Human Resources (HR) quality (H4), there is a significant influence of the role of Islamic banks on HR (H6), and there is a significant influence of HR on business development (H7). While indirectly the hypothesis that is accepted is H9, where the T statistic is 3.726 > 1.65, and the P values ​​are 0.00 <0.05, with Std. Beta is 0.367. It means that there is a positive influence of business capital on business development, mediated by the variable quality of Human Resources (HR).